Journalism for integration - Codina, Mónica (Javnost (Ljubljana), 2007)
In September 2005 the Danish newspaper Jyllands-Posten published 12 cartoons that poked fun at Islam. In January 2006 this resulted in an explosion of angry mass protest in Muslim countries. This was part of a political-cultural confrontation in which the press became involved when they decided to publish the cartoons in defence of freedom of speech. This case study throws some light on the elements, which gave rise to the controversy and have inspired similar incidents. The global dimension of the media action together with the growth of cultural co-existence means that this study may be of some help in understanding journalistic practice.
Keywords: časniki; časopisi; svoboda govora; svoboda tiska; ethics; etika; strpnost; pravica do veroizpovedi